2022
DOI: 10.3390/vision6040075
|View full text |Cite
|
Sign up to set email alerts
|

Prosopagnosia, Other Specific Cognitive Deficits, and Behavioral Symptoms: Comparison between Right Temporal and Behavioral Variant of Frontotemporal Dementia

Abstract: Right temporal variant of frontotemporal dementia (rtv-FTD) represents an uncommon and recently described frontotemporal dementia (FTD) entity presenting with symptoms in many ways comparable to those of the frontal or behavioral variant of FTD (bv-FTD). The aims of this study were to explore the timing of cognitive and behavioral symptoms of rtv-FTD, and to compare the distinct cognitive deficits including prosopagnosia and behavioral symptoms of rtv-FTD patients with those observed in bv-FTD patients. We rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Furthermore, prosopagnosia was not consistently tested in the bvFTD and svPPA groups, possibly limiting its detection [ 25 ]. Previous studies have reported prosopagnosia in both bvFTD and svPPA cases, but at consistently reduced rates compared to what we have observed in our sbvFTD cohort [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, prosopagnosia was not consistently tested in the bvFTD and svPPA groups, possibly limiting its detection [ 25 ]. Previous studies have reported prosopagnosia in both bvFTD and svPPA cases, but at consistently reduced rates compared to what we have observed in our sbvFTD cohort [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 50%
“…Deficits in socioemotional functioning are prominent ( 6 , 11 ), as are difficulties with visual object recognition ( 20 ). In particular, inability to recognize faces (prosopagnosia) is a frequently reported symptom in rtvFTD ( 19 , 21 25 ). There are fewer studies of rtvFTD compared to svPPA, but in one report Chan and colleagues ( 17 ) found that anterior temporal atrophy in rtvFTD extended to the hippocampus, resulting in greater volume loss in the right hemisphere.…”
Section: Introductionmentioning
confidence: 99%